Regional Exploration and Characterisation of CO2 Storage Prospects in the Utsira-Skade Aquifer, North Viking Graben, North Sea - C. Lloyd; M. Huuse; B. J. Barrett; A. M. W. Newton (Earth Science, Systems and Society)
Subsurface CO2 storage is considered a key element of reducing anthropogenic emissions in virtually all scenarios compatible with limiting global warming to 1.5°C. The Utsira-Skade Aquifer (Utsira, Eir and Skade Formations), northern North Sea, has been identified as a suitable reservoir. Although the overall storage capacity of the full aquifer has been estimated based on regional data, it is lacking an integrated assessment of containment and internal heterogeneity, to identify optimal areas for injection and for calculation of site-specific storage capacities. A high-resolution, broadband 3D seismic reflection dataset, full waveform inverted velocity data and 102 exploration wells are utilised to provide a catalogue of CO2 storage prospects in the northern Utsira-Skade Aquifer. This is achieved through: 1) definition of the aquifer’s spatial limits; 2) calculation of porosity distribution; 3) assessment of the extent, geomorphology, thickness variability, and containment confidence (CC) of mudstones; and 4) mapping of closures through fill-to-spill simulations. CO2 storage capacity was calculated for the prospects using two approaches; using the full reservoir thickness (FRT) beneath the closures and using only the thickness from the closure top to the spill point (TSP), i.e., within structural traps. Porosity ranges from 29 to 39% across the aquifer and is higher in the Utsira and Eir Fms. relative to the underlying Skade Fm. The mudstone separating the Skade and Eir/Utsira Fm. has a thickness > 50 m, and is a potential barrier for CO2. Other intra-aquifer mudstones were mainly interpreted to act as baffles to flow. Structural traps at the top Utsira and Skade Fms. yield fifteen prospects, with criteria of > 700 m depth and FRT storage capacity of > 5 Mt CO2. They have a combined storage capacity of 330 Mt CO2 (FRT) or 196 Mt CO2 (TSP). Five prospects have a positive CC score (total capacity: 54 Mt CO2 FRT or 39 Mt CO2 TSP). Additional storage capacity could be achieved through more detailed analysis of the seal to upgrade the CC scores, or through use of a network of the mapped closures with a fill-to-spill approach, utilising more of the aquifer.